LOCAL DEVELOPMENT INITIATIVES IN SERBIA’S RURAL COMMUNITIES AS PREREQUISITE FOR THE LEADER IMPLEMENTATION: AGRICULTURAL ADVISORS’ PERCEPTIONS - Paraušić, Vesna; Kostić, Zorana; Subić, Jonel (Economics of Agriculture, 2023)
The Leader approach, as a national measure of rural development is still in the initial development phase in the Republic of Serbia. In the coming period, more intense support for the implementation of this measure is expected, from the national/regional/local budget and through the IPARD III 2021-2027 pre-accession support program. How effectively the available support funds will be used largely will depend on local stakeholders in rural communities, primarily citizens and civil society representatives, and the capacity of their development initiatives. Based on the perceptions of 118 agricultural advisors involved in the study and using descriptive statistics, one-way analysis of variance and Pearson’s coefficient, the authors found a moderately capacity of local development initiatives in rural communities in the Republic of Serbia that does not differ by the regions, as well as the moderate positive correlation between the quality of life and capacity of local development initiatives.